Optimal allocation of battery energy storage system using WOA-AIS considering net load issue - Wong L.A.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery storage; Electric batteries; Immune system; Location; Particle swarm optimization (PSO); Artificial Immune System; Duck curve; Loss reduction; Optimal locations; Optimal size; Optimization algorithms; Overall system loss reduction; System loss; Whale optimization algorithm and artificial immune system; Curve fitting